FINE STRUCTURAL ANALYSIS OF UNPRODUCTIVE AND LOWPRODUCTIVE CELLS RESULTING ON CULTURED RSIV (IN VITRO) - Ketut Mahardika; Teruo Miyazaki (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2014)
Red seabream iridovirus (RSIV) has been known to induce enlarged cells and inclusion body bearing cells (IBCs) allowing virus particles to propagate within viral assembly site (VAS) in the cell cytoplasm. The aim of this study was to evaluate fine structural analysis of unproductive and low-productive cells resulting on RSIV-infected cultured grunt fin (GF) cells. GF cells were treated with semi purified RSIV, and incubated for 6-14 days post cultured. The cellular enlargement were harvested, processed, and analysis under electron microscopy. Electron microscopy revealed four types of cells that were productive enlarged cells and productive IBCs which were allowing propagation of virus particles within its cytoplasm, and unproductive enlarged cells and IBCs without virus particles. Most of them were unproductive enlarged cells (80,71%-98,20%). Unproductive enlarged cell had a nucleus with enlarged cytoplasm without production of VAS with virus propagation. While, unproductive IBC had an inclusion body that was delimited from the host-cell cytoplasm by a thin membranous boundary, and was developed without virus propagation. On the other hand, lowproductive enlarged cells and IBCs contained a few number of virus particles or tubule-like structures. Therefore, the number of low-productive enlarged cells and IBCs were only a few (about 0%-14% from a total of percent productive enlarged cells and IBCs), these cells were classified into types of productive enlarged cells and IBCs. These results sugested that the unproductive and low-productive enlarged cells and IBCs were the results of RSIV-infected GF cells which failed to produce virus particles due to incapacity of RSIV virus it self and or the ability of GF cells to inhibit virus multiplication within VAS.